1995
DOI: 10.1203/00006450-199502000-00017
|View full text |Cite
|
Sign up to set email alerts
|

The Relative Roles of External Taurine Concentration and Medium Osmolality in the Regulation of Taurine Transport in LLC-PK1 and MDCK Cells

Abstract: Taurine is a l3-sulfonic amino acid that serves as a nutrient important for developing brain and retina and as an osmolyte in the medullary collecting duct. The activity of the taurine transport system is regulated by substrate supply and by the external osmolality; these two stimuli induce changes in taurine transport. Increased medium osmolality (500 mosmol) stimulates taurine uptake into MDCK cells but not LLC-PKI cells. The enhanced taurine uptake that occurs in response to hyperosmolality is localized pri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

1999
1999
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 16 publications
1
21
0
Order By: Relevance
“…The contribution of taurine transport dependens upon the expression level and regulation of a taurine transporter (TauT), but also upon taurine level in extracellular medium. Increased maximal veliocity of taurine transport and increased levels of TauT mRNA have been consistently reported in a great variety of cells exposed to a hypertonic medium [49,50]. In the present study, we found that taurine plus endotoxin administration increased levels of taurine more, and the maximal mean of taurine level was seen in the taurine?endotoxemia group.…”
Section: Discussionsupporting
confidence: 55%
“…The contribution of taurine transport dependens upon the expression level and regulation of a taurine transporter (TauT), but also upon taurine level in extracellular medium. Increased maximal veliocity of taurine transport and increased levels of TauT mRNA have been consistently reported in a great variety of cells exposed to a hypertonic medium [49,50]. In the present study, we found that taurine plus endotoxin administration increased levels of taurine more, and the maximal mean of taurine level was seen in the taurine?endotoxemia group.…”
Section: Discussionsupporting
confidence: 55%
“…Phylogenetic analysis showed that this transporter belonged to the clade of mollusks TAUT. The activity and mRNA expression of TAUT were demonstrated to be inhibited by exogenous taurine supplementation, but were not modulated by glycine, alanine, or glutamic acid (Uchida et al, 1992; Jones et al, 1995; Han et al, 1997, 1998; Bitoun and Tappaz, 2000a,b; Takeuchi et al, 2000, 2001; Inoue et al, 2008). As others bivalves, e.g., deep-sea mussel, Mediterranean blue mussel, and Pacific giant oyster, the TAUT expression was detected in gills and mantles in the hard clam (Hosoi et al, 2005, 2007; Inoue et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…The natriuretic activity of taurine has been attributed to its osmoregulatory activity in the kidney, its modulation of atrial natriuretic factor secretion, and its putative regulation of vasopressin release (Dlouha and McBroom, 1986;Miyata et al, 1997;Mozaffari et al, 1997). It can also be attributed to the excretion of taurine, resulting in less reabsorption of Na Ï© and Cl ÏȘ across the renal epithelium (Zelikovic et al, 1989;Jones et al, 1995). Thus, taurine can cause a net loss of sodium without eliciting an extracellular volume expansion.…”
Section: Diuretic Effects Of Taurinementioning
confidence: 99%